2013
DOI: 10.1177/0956797612459657
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Recognition of Happiness in Ambiguous Facial Expressions Reduces Anger and Aggressive Behavior

Abstract: The ability to identify emotion in other people is critical to social functioning. In a series of experiments, we explored the relationship between recognition of emotion in ambiguous facial expressions and aggressive thoughts and behavior, both in healthy adults and in adolescent youth at high risk of criminal offending and delinquency. We show that it is possible to experimentally modify biases in emotion recognition to encourage the perception of happiness over anger in ambiguous expressions. This change in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
212
4
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 161 publications
(234 citation statements)
references
References 27 publications
(34 reference statements)
17
212
4
1
Order By: Relevance
“…(2012) and Penton‐Voak et al . (2013) to run the training paradigm on a Windows PC with a 19″ LCD monitor panel (1,600 × 1,200 native pixel resolution, 32‐bit colour depth). Each trial of the baseline and training conditions began with a central fixation cross which was shown for 1,500–2,500 ms (randomly jittered).…”
Section: Studymentioning
confidence: 99%
See 3 more Smart Citations
“…(2012) and Penton‐Voak et al . (2013) to run the training paradigm on a Windows PC with a 19″ LCD monitor panel (1,600 × 1,200 native pixel resolution, 32‐bit colour depth). Each trial of the baseline and training conditions began with a central fixation cross which was shown for 1,500–2,500 ms (randomly jittered).…”
Section: Studymentioning
confidence: 99%
“…This approach has been developed from a face training programme, used to modify biases in emotion recognition in order to encourage the perception of happiness over anger in ambiguous expressions in adolescents who are at high risk of criminal offending and delinquency (Penton‐Voak et al ., 2013). In the original study, participants were presented images of faces and had to make a two‐alternative forced choice (2‐AFC) decision whether a particular face was happy or angry.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…One such methodology is aimed at modifying perceptual biases in categorization of ambiguous facial expression. Perceptual biases in facial expression categorization have been associated with exposure and social experiences (e.g., Pollak et al, 2009) and have been observed in people with major depression (Joormann and Gottlieb, 2006), in abused children (Pollak et al, 2009;Da Silva Ferreira et al, 2014) and in adolescents at high risk of aggression and delinquency (Penton-Voak et al, 2013).…”
Section: Introductionmentioning
confidence: 99%